Mechanistic Study of Tai Chi Intervention for Breast Cancer-Related Lymphedema Syndrome - Zhang, Siyuan; Fan, Yingyi; Wang, Chunyun; Xia, Xiaobin (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details